A Sweet Story: Bean pod mottle virus Transmission Dynamics by Mexican Bean Beetles (Epilachna varivestis) - Smith, Charlotte M. (Genome Biol Evol, 2017)
Worldwide crop losses due to plant diseases exceed $60 billion annually. Next to fungi, viruses represent the greatest contributor to those losses, and these are transmitted in nature primarily by insects. Mexican bean beetles (Epilachna varivestis) are formidable pests of soybean, as well as efficient vectors of several soybean-infecting viruses, including Bean pod mottle virus (BPMV). Beetle-borne viruses have a unique mode of transmission, though their interactions with host plants and vectors remain poorly understood. In these studies, we implemented targeted metabolite profiling and high throughput RNA sequencing approaches to explore metabolic and molecular changes in soybean leaves infected with BPMV. The virus-infected plants showed altered defence signaling and amino acid concentrations—and most strikingly—had dramatically higher sucrose levels. Based on the results, we performed a series of E. varivestis behavioral bioassays using near-isogenic soybean lines of differing foliar sucrose levels in an attempt to more directly associate sucrose content and E. varivestis feeding preferences. Choice assays revealed E. varivestis is more attracted to BPMV-infected soybean than to healthy plants. Moreover, no-choice assays indicated that beetles consume less foliage per plant but ultimately feed on more plants in a given time period if they are higher in sucrose. Importantly, these virus-driven changes to beetle feeding preferences are likely to increase BPMV spread in natural environments.